Reconstruction of Legal Protection for Electronic Land Certificate Holders in The Context of Updating the Digitalbased National Land Law System in Indonesia - Muhammad Jeppry Lius; Bambang Soesatyo (CV. Green Publisher Indonesia, 2026)
In the context of modernizing Indonesia’s digitally based land law system, this study evaluates and reconstructs the legal protection afforded to holders of electronic land certificates. This study employs a normative juridical research method using statutory and conceptual approaches. The findings demonstrate that although Law Number 1 of 2024 concerning Electronic Information and Transactions and Government Regulation Number 18 of 2021 provide a legal foundation for electronic land certificates, the existing legal protection remains suboptimal because of regulatory disharmony, the absence of comprehensive data security standards, and limited infrastructure and public readiness. The study identifies several significant challenges, including the absence of specific regulations governing land data security standards and the vulnerability of electronic systems to cyberthreats. Furthermore, the lack of synchronization between the land law regime and information technology law creates normative ambiguity regarding the evidentiary status of electronic land certificates in judicial proceedings. This study proposes a comprehensive legal reconstruction through regulatory harmonization, the strengthening of digital security systems using technologies such as blockchain and multifactor authentication, and the development of a technology-based legal protection model that guarantees legal certainty and social justice. The proposed reconstruction model encompasses the reform of legal norms, the strengthening of digitally based protection systems, the development of integrated institutions and infrastructure, and the incorporation of fundamental legal values. Accordingly, this model provides a framework for reforming Indonesia’s national land law system to ensure that it remains adaptive and responsive to technological developments.